Secure and Customizable Data Management for Automotive Systems: A Feasibility Study. (18th March 2012) - Thüm, Thomas; Schulze, Sandro; Pukall, Mario; Saake, Gunter; Günther, Sebastian
Abstract : Custom tailor-made database management systems (DBMS) are an essential asset, especially for embedded systems. The continuously increasing amount of data in automotive systems and the growing network of embedded devices can profit from DBMS. Restrictions in terms of processors, memory, and storage require customizable DBMS that contain only the needed functionality. We present Auto Da Ma, a customizable DBMS designed for automotive systems. With Auto Da Ma, it is possible to generate tailor-made DBMS for different scenarios, for example, by restricting the storage size of the DBMS or adding security-related features such as asymmetric and symmetric encryption. We demonstrate the feasibility of our approach through applying different tailor-made DBMS versions derived from Auto Da Ma in an automotive testing environment. Our experience is that Auto Da Ma can dramatically reduce the development effort and can increase reliability using efficient reuse mechanisms.